Development of a Web-Based and Mobile Application System for Posyandu Services in Curug Sangereng Village - Monica Pratiwi; Irmawati; Nabila Husna Shabrina; Dinar Ajeng Kristiyanti; Monika Evelin Johan (Universitas Muhammadiyah Surakarta, 2026)
Pos Pelayanan Terpadu (Posyandu) is a form of Upaya Kesehatan Bersumberdaya Masyarakat (UKBM) managed by and for the community to facilitate access to basic health services. Desa Curug Sangereng, located in Kecamatan Kelapa Dua, Tangerang, Banten, has nine posyandu that serve and monitor the health of 14,311 residents. This activity is supported by posyandu members who act as health promoters and educators to encourage a clean and healthy lifestyle while recording residents' health data. In addition to on-site recording at the posyandu, members also conduct home visits for residents who are absent during service hours or undergoing outpatient care. Up to the present, the process of recording community health data has still been carried out manually using notebooks and simple forms. This practice often poses challenges, such as difficulties in data recapitulation and analysis, as well as limited access when data are required for reporting to Puskesmas. To address these challenges, an e-Posyandu application was developed as a web-based and mobile platform integrated with the village’s main website (curugsangereng.id). The application was developed using the waterfall method and equipped with features such as data input, health record history, and data export in multiple file formats. Following the development and deployment stages, socialization and training sessions were conducted to introduce the application to Posyandu members. User Acceptance Testing (UAT) was carried out with 35 members of Curug Sangereng Village through a questionnaire. The results showed that 94.3% of members on the website version and 88.6% on the mobile version could easily use the application. These findings indicate that the majority of posyandu members are able to utilize e-Posyandu effectively in supporting the process of health data recording and monitoring, although a small proportion still requires further assistance, particularly in using the mobile version.